From Remediation to Acceleration: Recruiting, Retaining, and Graduating Future Culturally and Linguistically Diverse (CLD) Educators - Herrera, Socorro G.; Morales, Amanda R.; Holmes, Melissa A.; Terry, Dawn Herrera (My University, 2011)
This ethnographic case study explores one mid-western state university's response to the challenge of culturally and linguistically diverse (CLD), especially Latino/a, student recruitment and retention. BESITOS (Bilingual/Bicultural Education Students Interacting To Obtain Success) is an integrated teacher preparation program implemented at a predominantly White university that seeks to both increase Latino/a students' initial access to higher education and provide institutional support to facilitate a high rate of graduation. The researchers consider key elements of the BESITOS program model as they relate to and support the sociocultural, linguistic, academic, and cognitive dimensions of the CLD student biography. For each dimension, the program model is first placed in the context of existing literature on CLD student education. The key elements and strategies of the program model used to successfully meet recruitment and retention goals are then discussed.